BAGAIMANA PERAN GURU MENDORONG SISWA MENJADI WARGA GLOBAL? PEMAHAMAN KERAGAMAN GLOBAL PADA GURU SEKOLAH INDONESIA DAN THAILAND - Syifa Siti Aulia; Avanti Vera Risti P; Ratri Nur Hidayati; Yulia Gesti Merkuri; Iqbal Arpannudin (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2024)
ABSTRACT This research focuses on two schools in Indonesia, Aisyiyah Nur'aini Integrated Preschool and Suan Santi School, both of which have a responsibility to teach character development. Both schools have similar learning environments, both in Indonesia and in Thailand, which has a rich cultural heritage. The partners are also schools that focus on Islamic teachings in ECD. This study highlights the importance of understanding the differences between schools as this is a key goal of education to foster a sense of belonging and diversity. Suan Santi School in Thailand is a school for Muslims as a minority, yet the study shows that the majority of students in this school face threats from Buddhist sects, intimidation and violence. To provide knowledge about global awareness, new knowledge is needed from the teachers. In Indonesian and Thai schools, diversity is a distinctive feature that reflects the multicultural and multiethnic societies in which the schools are located. Students come from different backgrounds, religions and cultures, creating diverse experiences and perspectives within the school community. This research looks at two perspectives: the importance of diversity being taught by teachers, and the importance of embracing global diversity.